Photogrammetric state of degradation assessment of decorative claddings: the plasterwork of the Maidens' Courtyard (The Royal Alcazar of Seville) - Marta Torres-González; Elena Cabrera Revuelta; Ana I. Calero-Castillo (Virtual Archaeology Review)
Highlights: